2005
DOI: 10.1097/01.mcg.0000174023.73472.29
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Chronic Hepatitis C Virus Infection via Antioxidants

Abstract: These data suggest that multi antioxidative treatment in chronic HCV patients is well tolerated and may have a beneficial effect on necro-inflammatory variables. A combination of antiviral and antioxidative therapies may enhance the overall response rate of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
85
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(89 citation statements)
references
References 41 publications
3
85
0
1
Order By: Relevance
“…Previous studies suggested that LA acts as an antiinflammatory agent in vivo and plays a role in cardiovascular protection (27)(28)(29), although LA's mechanism of action remained unclear. Our results suggest a mechanism by which LA activates the PI3K/Akt signaling pathway and consequently inhibits NF-B activity, expression of proinflammatory mediators, and septic lethality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies suggested that LA acts as an antiinflammatory agent in vivo and plays a role in cardiovascular protection (27)(28)(29), although LA's mechanism of action remained unclear. Our results suggest a mechanism by which LA activates the PI3K/Akt signaling pathway and consequently inhibits NF-B activity, expression of proinflammatory mediators, and septic lethality.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to playing an important role in mitochondrial energy metabolism, LA and dihydrolipoic acid can scavenge reactive oxygen species, regenerate physiological antioxidants, chelate metal ions, and stimulate insulin signaling (23)(24)(25). Lipoic acid significantly improves diabetic neurovascular and metabolic abnormalities (26) and may play a role in cardiovascular protection and as an antiinflammatory agent (27)(28)(29)(30). Using cultured human aortic endothelial cells, we have shown that LA inhibits TNF␣-or LPS-induced expression of CAMs and MCP-1 and subsequent monocyte-endothelial interactions (11).…”
mentioning
confidence: 99%
“…In this regard, it should be noted that oxidative and nitrosative stress may possess diverse effects on cell growth and apoptosis [108]. As a consequence, antioxidants have been proposed as an adjunct therapy for chronic hepatitis C [109].…”
Section: Viral Hepatitis and Free Radicalsmentioning
confidence: 99%
“…These lignans are abundant in the seeds and fruits of SC (Huang et al, 2007;Ikeya et al, 1979;Lu et al, 2009;Panossian et al, 2008;Slanina et al, 1997). Previous studies have shown that SC possesses neuroprotective effects on glutamate-induced apoptosis (Lee et al, 2012) and has the ability to protect the liver from injury induced by toxins substances, such as, those associated with hepatitis (Liu, 1989;Melhem et al, 2005). Schizandrin B and C are components of SC extract (Xu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%